Development of Economics Teaching Materials Based on Entrepreneurial Values as A Learning Media - Mispandi Mispandi; Muh. Fahrurrozi (Universitas Negeri Semarang, 2023)
The aims of this study were (1) to develop teaching materials based on entrepreneurial values; (2) to find out the feasibility of teaching materials according to media experts, material experts, and student responses. This research is a study on the development of economic teaching materials based on entrepreneurial values ​​as a source of learning using research methods (Research and Development). The research method uses R&D (Educational Research and Development) which consists of stages namely potential problems, planning, product design, design validation, revision, trial and final product. The results of the development on material assessment obtained presentation results of 92% in the very appropriate category, the design assessment on the media obtained presentation results of 92% in the very feasible category, and the assessment of students' responses to teaching materials obtained presentation results of 93% in the very feasible category. Thus, from the results of research at SMAN 1 Sukamulia, it can be concluded that this teaching material is suitable for use in class XI students.